At the Crossroads of Life: Belgraders’ Perceptions of Their Old Age - Senka Kovač (Etnoantropološki Problemi, 2016)
The paper presents the results of several years’ fieldwork among the elderly population in Belgrade. The study examines the attitudes towards old age of elderly Belgraders living alone, those living with their families, and also those living in the Gerontology Center nursing home. The position of elderly people in the social network in the Belgrade municipality of Vračar is also explored. In this era of longevity and at a time of global economic crisis which is also affecting Serbia, it would be useful to reconsider the concepts of successful aging, well-aging and healthy aging.